Critical Appraisal of Published Literature in Specialty General Surgical Examinations in the United Kingdom - Shrestha, Badri Man (Journal of Nepal Health Research Council, 2018)
The specialty general surgical examination in the United Kingdom, which needs to be qualified by the higher surgical trainees towards the end of their training prior to assuming consultant responsibility, includes “academic foundation viva” as a mandatory component. This section of examination is intended to assess candidate’s ability to critically appraise published literature with regards to its validity and clinical relevance, which is essential requirement for a surgeon to be able to deliver care to his patients based on robust evidence collected from properly conducted studies. The paper aims to outline the objectives of the assessment process, the details of appraisal methodology and techniques to acquire the skill.